BRAND POSITIONING STRATEGY THROUGH DIGITAL MARKETING OF COMMERCIAL RICE PRODUCTS AT PERUM BULOG JEMBER BRANCH - Wibowo, Yuli; Purnomo, Bambang Herry; Salsabila (Department of Agroindustrial Technology, Bogor Agricultural University, 2024)
The development of information technology, especially in digital marketing, has brought significant changes in how companies interact with consumers and build company brand images, including Perum BULOG Jember Branch. This research aims to increase awareness of the